Alley-Farming Network established - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1989)
The Alley Farming Network for Tropical Africa (AFNETA) which began operations in February 1989 brings together three international institutes: ITA (the International Institute of Tropical Agriculture), which coordinates the work, ILCA (the...